Assessment of the mechanical and tribological performance of a ZrN PVD coating. (3rd June 2019) - Staia, M. H.; Trocelis, A.; Zairi, A.; Suarez, M.; Puchi-Cabrera, E. S.; Iost, A.; Montagne, A.
ABSTRACT: The present work has been conducted in order to assess the mechanical and tribological performance of a ZrN/Mo2 N coating deposited onto a H13 steel by means of a closed field unbalanced magnetron-sputtering ion-plating process. The hardness and elastic modulus of the coated system have been determined employing nanoindentation techniques. Dry and wet (3.5 wt-% NaCl solution) sliding wear tests were carried out making use of an alumina ball as counterpart. It has been determined that, during testing under the corrosive solution, the coating experiences a severe abrasive wear mechanism, due to the combined action of the alumina ball, the hard 'debris' and a coating localised corrosion attack. On the other hand, it has been shown that the coated system is able to increase the wear resistance of the substrate by more than one order of magnitude, if the wear tests are carried out in air under the same conditions.